Biofilmed-PGPR: Next-Generation Bioinoculant for Plant Growth Promotion in Rice under Changing Climate - Jeberlin Prabina Bright; Hemant S. Maheshwari; Sugitha Thangappan; Kahkashan Perveen; Najat A. Bukhari; Debasis Mitra; Riyaz Sayyed; Andrea Mastinu (Rice Science)
The exopolysaccharide matrix of diazotrophic cyanobacteria was used to integrate phosphorus (P) and potassium (K) solubilizing bacteria, enhancing the survival of plant growth-promoting rhizobacteria, and ultimately the survival of bacteria in the rhizosphere for better plant growth. A new biofilm-based formulation comprising the diazotrophic cyanobacteria Anabaena AMP2, P-solubilizing Bacillus megaterium var. phosphaticum PB1, and K-solubilizing Rhizobium pusense KRBKKM1 was tested for efficacy in rice. The growth medium with half-strength BG-11 medium supplemented with 3% glucose showed best for biofilm formation under in vitro conditions. Analysis of the methanolic extract of the cyanobacterial- bacterial biofilm (CBB) showed the activity of antioxidants, such as 2-methoxy phenol and pentadecane, which are proven to improve plant-microbe interactions and plant growth, respectively. Treatment of rice seeds with CBB extract at 100 mL/kg or 200 mL/kg showed significant enhancement in germination rate and seedling length. Therefore, a pot culture experiment with the CBB formulations was carried out, and different growth and yield parameters were recorded. Principal component analysis showed that plant growth, yield, soil dehydrogenase activity, and soil chlorophyll content were positively correlated with rice plants amended with vermiculite-based CBB at 2 kg/hm2 followed by a spray with aqueous CBB formulation at 5 mL/L at 15 and 30 d after rice transplanting grown with a 25% reduced level of nitrogen/phosphorus/potassium chemical fertilizers than the recommended dose. Further, Pearson correlation analysis showed that yield was positively correlated with soil dehydrogenase (r = 0.92**) and soil chlorophyll content (r = 0.96**). We concluded that CBB could be used as a novel biofilm-based bio-inoculant to increase rice productivity and crop fitness as a component in integrated nutrient management and sustainable organic farming strategies with reduced chemical fertilizers.